Pengetahuan, Fitur Produk Dan Kebutuhan Produk Terhadap Keinginan Mengunakan Jasa Layanan Bank Syariah di Pondok Pesantren - Nasfi Nasfi; Okfi Resti; Asnah Asnah; Eka Febrianti; Suhatman Suhatman (IAIN Batusangkar, 2023)
Sharia banking as a national asset grows 9.22% in 2020 in Muslim-majority countries, the aim of this research is to find out the effect of knowledge, product features and the need for the desire to use sharia banking financing and funding products in the city of Padang Panjang, which is predominantly a Muslim community. This type of descriptive quantitative research using a questionnaire technique, the population of Islamic boarding school teachers is 211 people and the research sample is 138 people, multiple linear analysis techniques. Analysis with validity, reliability and multiple linear regression analysis techniques. Research results individually have no significant effect on making prospective customers use Islamic bank services, but prospective customers want to use Islamic banking services because there is a need for bank products